Dermatofibrosarcoma Protuberans in a Child: A Case Report. (18th December 2012) - Goyal, Prashant; Sehgal, Shelly; Singh, Sompal; Rastogi, Shalabh
Abstract : Background . Dermatofibrosarcoma protuberans (DFSP) is an intermediate grade soft tissue neoplasm originating from the dermal layer of the skin. It usually occurs in adults; however, it can rarely be seen in infancy and childhood. Diagnosis of DFSP in children is quite difficult-given-rarity of this lesion, its variegated appearance, and its presentation sometimes at unusual sites. Case . We present the case of five-year-old boy who came with painless lesion on a forehead. Fine needle aspiration cytology (FNAC) suggested possibility of mesenchymal neoplasm. Patient was advised excision biopsy. Final diagnosis of DFSP was made based on histopathological findings. The patient was then advised reexcision surgery with wide margins. The patient was lost to followup and later turned up after two months with recurrence of a similar swelling at the same site. Conclusion . DFSP in children is rare and difficult to diagnose. Treatment of childhood DFSP is often delayed leading to incomplete excision. Hence, there is need to recognize and appropriately manage this uncommon childhood neoplasm.